Vacancies, Unemployment, and the Phillips Curve - Federico Ravenna; Carl E. Walsh (Kiel Institute for the World Economy (IfW), 2007)
The canonical new Keynesian Phillips Curve has become a standard component of models designed for monetary policy analysis. However, in the basic new Keynesian model, there is no unemployment, all variation in labor input occurs along the intensive hours margin, and the driving variable for inflation depends on workers' marginal rates of substitution between leisure and consumption. In this paper, we incorporate a theory of unemployment into the new Keynesian theory of inflation and empirically test its implications for inflation dynamics. We show how a traditional Phillips curve linking inflation and unemployment can be derived and how the elasticity of inflation with respect to unemployment depends on structural characteristics of the labor market such as the matching technology that pairs vacancies with unemployed workers. We estimate on US data the Phillips curve generated by the model, and derive the implied marginal cost measure driving inflation dynamics.
Keywords: E58; E52; J64; 330